1985
DOI: 10.1210/jcem-60-1-156
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial and Pituitary Responses to the Steroidal Antiprogestin RU 486in Postmenopausal Women

Abstract: The effects of the antiprogestin RU 486 on the human endometrium were investigated. Seventeen postmenopausal women were injected with estradiol (E2) benzoate (0.625 mg/day) for 15 days. Progesterone (P) (25 mg/day) and/or RU 486 (100 or 200 mg/day) were given to groups of 2-3 women during the last 6 days of E2 benzoate treatment. Serial blood samples were drawn for the measurement of plasma E2, P, and LH and FSH. An endometrial biopsy was performed on the last day of treatment, and processed for histology or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
1
6

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(38 citation statements)
references
References 18 publications
(16 reference statements)
5
26
1
6
Order By: Relevance
“…In our system, we found that Mifepristone has weak agonist activity, mediating PSA gene up-regulation at concentrations .10-8 M. This agonist activity was not observed by Philibert et al (1985), further suggesting that their biological tests are not as sensitive as our tissue culture system in detecting such an effect. In support of our data are reports by others showing weak agonist activity of RU486 in various systems (Gravanis et al, 1985;Gronemeyer et al, 1991;Wehle et al, 1995). It remains to be seen if the weak agonist activity of mifepristone is mediated by the androgen, glucocorticoid or the progesterone receptor.…”
Section: Discussionsupporting
confidence: 92%
“…In our system, we found that Mifepristone has weak agonist activity, mediating PSA gene up-regulation at concentrations .10-8 M. This agonist activity was not observed by Philibert et al (1985), further suggesting that their biological tests are not as sensitive as our tissue culture system in detecting such an effect. In support of our data are reports by others showing weak agonist activity of RU486 in various systems (Gravanis et al, 1985;Gronemeyer et al, 1991;Wehle et al, 1995). It remains to be seen if the weak agonist activity of mifepristone is mediated by the androgen, glucocorticoid or the progesterone receptor.…”
Section: Discussionsupporting
confidence: 92%
“…Such an effect could not be demonstrated in the monkey (Healy et al, 1983;Asch and Rojas, 1985). On the other hand, RU486 administered to normal women, in the mid-luteal phase of the menstrual cycle (Schaison et al, 1985) and to postmenopausal women (Gravanis et al, 1985), resulted in a decrease in mean LH levels and the disappearance of pulsatile release. It is noteworthy, however, that in women with anovulatory cycles no effect on LH could be observed (Schaison et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…There has been increasing interest in the development of antiprogestins for both anti-neoplastic and obstetrical applications (Cadepond et al, 1997;Gravanis et al, 1985;Rocereto et al, 2000). However, some of the progesterone antagonists can have undesired agonist-like effects that are associated with cell, tissue and species specificity.…”
mentioning
confidence: 99%
“…However, some of the progesterone antagonists can have undesired agonist-like effects that are associated with cell, tissue and species specificity. For example, RU486 has been reported to have agonist-like activities in postmenopausal women, as well as in numerous in vitro studies, under conditions in which inhibition would be expected (Gravanis et al, 1985;Meyer et al, 1990;Nordeen et al, 1993). The clinical consequences of the inappropriate agonist-effect of an antagonist can be grave.…”
mentioning
confidence: 99%